2008
DOI: 10.2174/092986708786848659
|View full text |Cite
|
Sign up to set email alerts
|

New Inhibitors of Glycogen Phosphorylase as Potential Antidiabetic Agents

Abstract: The protein glycogen phosphorylase has been linked to type 2 diabetes, indicating the importance of this target to human health. Hence, the search for potent and selective inhibitors of this enzyme, which may lead to antihyperglycaemic drugs, has received particular attention. Glycogen phosphorylase is a typical allosteric protein with five different ligand binding sites, thus offering multiple opportunities for modulation of enzyme activity. The present survey is focused on recent new molecules, potential inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
132
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 147 publications
(226 reference statements)
1
132
0
2
Order By: Relevance
“…As it was anticipated, the difference electron density maps (Figure 1, right) confirmed that compound 22 also binds at the catalytic site of the enzyme and the 2-naphthyl group is accommodated in the so-called β-subsite, in accordance with previous compounds with such a substituent. 2 A portion of additional electron density was observed at the new allosteric site of the enzyme that could be attributed to the 2-naphthyl group only. Previous studies have shown that glucose analogues bearing this group bound at both the catalytic and the new allosteric site.…”
Section: Crystallographic Studiesmentioning
confidence: 96%
See 3 more Smart Citations
“…As it was anticipated, the difference electron density maps (Figure 1, right) confirmed that compound 22 also binds at the catalytic site of the enzyme and the 2-naphthyl group is accommodated in the so-called β-subsite, in accordance with previous compounds with such a substituent. 2 A portion of additional electron density was observed at the new allosteric site of the enzyme that could be attributed to the 2-naphthyl group only. Previous studies have shown that glucose analogues bearing this group bound at both the catalytic and the new allosteric site.…”
Section: Crystallographic Studiesmentioning
confidence: 96%
“…17,22 In this series X-ray crystallography of the enzymeinhibitor complexes 2,23 indicated the absence of the above mentioned hydrogen bond between the β-NH group and His377 O; therefore, the stronger binding was attributed to extensive interactions with the large aromatic appendage of the inhibitor in the so-called β-channel of the protein. A variant of E with a 3,5-dimethyl-phenyl group in place of the 2-naphthyl moiety was shown to improve glucose tolerance and to rearrange hepatic metabolism in diabetic mice.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…9,10 GPIs comprise a very broad array of compounds with high structural diversity due to the peculiarities of several binding clefts (the catalytic, allosteric and new allosteric, inhibitor, glycogen storage, benzimidazole, and quercetin sites) discovered so far. 11,12 Several nanomolar inhibitors with various heterocyclic scaffolds, amply discussed in review articles, 11,12 bind to the allosteric or the new allosteric sites of GP. The most populated class of GPIs is represented by glucose derivatives, which bind primarily to the catalytic site of the enzyme showing competitive inhibition.…”
mentioning
confidence: 99%